TINJAUAN TERHADAP KOMPETENSI DAN INDEPENDENSI AKUNTAN PUBLIK : REFLEKSI ATAS SKANDAL KEUANGAN - Hexana Sri Lastanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2005)
Scandal happened in most of big companies it generally started by the published financial statement. The scandal actors have usually prepare some tricks so that the published financial statements suit the last goal of their crime motif. In this case, the question is, can the auditors of the financial statements detect these tricks? Or, has it been detected but the auditors let the crime run.The competences or public accountants cover the knowledge component, psychology characteristics, thinking ability, determination of decision strategy, and duty analysis. The independency of public accountant cover mental attitude, independency, and appearance independency. If that happened is auditor unable to detect the tricks financial statement engineering, hence core of its problems is auditor competences. But if that happened is the auditors protect to crime, hence core of its problems is auditor independency.